The impact of government failure on tourism in the Philippines - Manuela, Wilfred S, Jr (Archīum Ateneo, 2015)
While the Philippines aspires to be one of the top tourist destinations in Southeast Asia, self-inflicted wounds like the failure of the government to comply with international aviation safety standards may derail the country from achieving its goals. This article estimates the short- and long-term impact of the US FAA downgrade of the Philippine civil aviation system in 2008 and the EU ban of Philippine carriers in 2010 on tourist expenditures, arrivals, and length of stay using monthly time series data. The econometric model, consisting of three equations due to the endogeneity of the tourist arrivals and length of stay variables in the tourist expenditures equation, is estimated simultaneously using the generalized method of moments. The results indicate that the US FAA downgrade and the EU ban impact monthly tourist receipts negatively in the short term while the downgrade also impacts tourist expenditures in the long term. Moreover, the ban impacts length of stay negatively in the short and long term while the downgrade impacts length of stay negatively only in the long term. The substantial decline in tourism receipts from 2008 to 2010 despite an increasing trend in tourist arrivals is due to the shorter stay of tourists, indicating that high-spending tourists have not returned following the downgrade and ban.